Robust extended Kalman filter based nonlinear model predictive control formulation - Rui Huang; Patwardhan, S.C.; Biegler, L.T. (Proceedings of the 48h IEEE Conference on Decision and Control (CDC) held jointly with 2009 28th Chinese Control Conference, 2009)
The analysis of the EKF error sequence in is expanded to the case with non-vanishing perturbations. The robust stability of NMPC and EKF pair is established. In addition, we propose an output-feedback NMPC formulation based on both the prior and posterior errors of the EKF to achieve offset-free regulatory control behavior.